Influence of resistive load on power output and fatigue during intermittent sprint cycling exercise in children - Bogdanis, G. C.; Papaspyrou, A.; Theos, A.; Maridaki, M. (European Journal of Applied Physiology, 2007)
This study examined the effects of two resistive loads on fatigue during repeated sprints in children. Twelve 11.8 (0.2) year old boys performed a force-velocity test to determine the load (Fopt) corresponding to the optimal pedal rate. On two separate occasions, ten 6-s sprints interspersed with 24-s recovery intervals were performed on a friction-loaded cycle ergometer, against a load equal to Fopt or 50%Fopt. Although mean power output (MPO) was higher in the Fopt [397 (24) and 356 (19) W, P < 0.01], the decline in MPO over the 10 sprints was similar in Fopt [8.8 (1.9) %] and 50%Fopt [9.0 (2.4) %]. In contrast, peak power (PPO) was not different in sprint 1 between the two conditions [459 (24) and 460 (28) W], but was decreased only in 50%Fopt [11.4 (3.2) %, P < 0.01], while it was maintained in the Fopt despite the higher total work during each sprint. Fatigue within each sprint (percent drop from peak to end power output) was also higher in the 50%Fopt compared with the Fopt [32 (2.5) vs. 10 (1.6) %, P < 0.01]. Peak and mean pedal rate in Fopt condition were close to the optimum (Vopt), while a large part of the sprint time in 50%Fopt was spent far from Vopt. The present study shows that sprinting against Fopt reduces fatigue within and between repeated short sprints in children. It is suggested that fatigue during repeated sprints is modified when pedal rate is not close to Vopt, according to the parabolic power versus pedal rate relationship.